Pengembangan Plugin QGIS Untuk Mengakses Peta Geologis Seluruh Indonesia - Mukhamad Misbakh Alif; Fatwa Ramdani; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Natural disasters in almost every season hit Indonesia such as floods, landslides, fires and puso. Floods and landslides usually occur in the rainy season while fires and puso occur in the dry season. At present the frequency of floods and landslides increases as well as fires and pusos. Other natural disasters that often occur are geological disasters, such as earthquakes. Earthquakes in Indonesia often occur because they are flanked by three main plates namely the Indo-Australian plate. Eurasian Plate, and Pacific Plate. Efforts made to date use personal websites to disseminate geological map information. However, this business is still not neatly arranged. Meanwhile the Bandung Geological Directorate Agency does not have an official portal while the public can access geological maps throughout Indonesia. For this reason, plugins are developed from open source applications that can see geological maps throughout Indonesia in the form of plugins. Among the plugins developed by researchers are the Geological Map plugins. The Geological Map Plugin is an additional QGIS application that uses the Python programming language as the basis for making it. This plugin has a function to display the Geological Map of All of Indonesia. This geological map plugin can help find out the geological information of the region in Indonesia.